Investigation of gut microbiota diversity according to infectious agent in pediatric infectious acute gastroenteritis in a Korean university hospital - You Ie Kim; Sang Yong Kim; Seungok Lee; Myungshin Kim; Woo Jin Kim (Elsevier, 2024)
Background: Acute gastroenteritis (AGE) is a common cause of pediatric morbidity and mortality worldwide. AGE can cause an imbalance in the intestinal microbiota. This study aimed to investigate the diversity of the gut microbiome in Korean children hospitalized for infectious AGE at a university hospital. Methods: A total of 23 stool samples from patients aged 5 months to 11 years with AGE were analyzed. Thirteen convalescent stool samples were collected 1 month after discharge. Multiplex polymerase chain reaction (PCR) for the five viruses and 16 bacteria-specific AGE pathogens (PowerChek Multiplex Real time PCR Kit, Seoul, Korea), and 16s rRNA sequencing (Illumina MiSeq Sequencing system, Illumina, USA) were performed. Results: According to the results of multiplex PCR for causative pathogens, the microbiome taxonomic profile (MTP) of the gut microbiome in three groups of AGE, norovirus AGE (n = 11), Campylobacter AGE (n = 7) and Salmonella AGE (n = 5) was compared. The phylum Actinobacteria was significantly more abundant in the norovirus AGE (P = 0.011), whereas the phylum Proteobacteria was significantly more abundant in Salmonella AGE (P = 0.012). Alpha diversity, which indicates species richness and diversity, showed no statistical differences. However, beta diversity, representing the similarity in MTP between norovirus, Campylobacter, and Salmonella AGE, was significantly different (P = 0.007). In convalescence, compared with their corresponding AGE samples, the phylum Firmicutes; and the lower taxa Christensenellaceae (P = 0.0152) and Lachnospiraceae (P = 0.0327) were significantly increased. Conclusions: In pediatric AGE, the type of infectious agent can affect the diversity and dominance of gut microbiota in pediatric patients. Furthermore, healthy gut bacteria increased during the period of 1 month after infection, allowing a return to a healthy state without causing long-term dysbiosis.